Fotobiomodulação em incisão cutânea ocasionada pelos fios e pinos do aparelho fixador externo circular Ilizavov: estudo clínico, placebo duplo cego, controlado e randomizado - Rodrigues, Virginia Mendes Matias (2020)
In Brazil, thousands of musculoskeletal surgeries are performed annually, and this high number of procedures has a social and economic impact for the country. The Ilizarov-type circular external fixator (FEC) is a device used for reconstruction of severely traumatized limbs, when other methods, such as pressure and intraosseous plates, cannot obtain or obtain expected success. Although bone tissue is the target during treatment with this type of device, surgical incisions caused by the insertion of its wires and / or pins deserve attention so that the healing process proceeds in the best possible way, reducing pain and the possibility of skin infection. The objective of the study was to use photobiomodulation (FBM) in incision caused by the use of FEC (in the insertions of wires and pins) and to collect clinical evidence using the BWAT scale, visual analog scale of pain, temperature and pH of the lesion, as well as as the time of recurrence of the lesion after the end of treatment in relation to the conventionally treated group. It was a clinical study, double blind, placebo controlled and randomized, composed of 5 participants in the placebo-controlled group and 5 in the photobiomodulation group. All received a dressing with 0.9% saline plus fatty acids, but one group was truly irradiated, while the other received placebo irradiation. The interventions took place from the 3rd postoperative period, every 72 hours, for 3 months. A laser was used, λ = 660nm, beam area on the surface of 0.126cm2, I = 796mW / cm2, H = 4J / cm2, t = 5s, E = 0.5J, 4 points per injury. According to the BWAT scale, the FBM group showed a significant improvement in the wounds from day 6 of the analysis, as well as a decrease in pain between days 2 and 8, and then on day 13. The pH and temperature were significantly lower in the FBM group on days 6 and 7, and day 8, respectively. There was clinical evidence of improvement in lesions treated with FBM compared to the controlled placebo group. There was no response in either group and two participants in the FBM group evolved as well as they retired or FEC ahead of schedule.